Orbital superexchange and crystal field simultaneously at play in YVO 3: resonant inelastic x-ray scattering at V L edge and the O K edge - Benckiser, Eva; Schmitt, Thomas; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2013)
We report on the observation of orbital excitations in YVO3 by means of resonant inelastic x-ray scattering (RIXS) at energies across the vanadium L3 and oxygen K absorption edges. At the V L3 edge, we are able to resolve the full spectrum of orbital excitations up to 5 eV. In order to unravel the effect of superexchange interactions and the crystal field on the orbital excitations, we analyzed the energy and temperature dependence of the intra-t2g excitations at 0.1-0.2 eV in detail. While these results suggest a dominant influence of the crystal field, peak shifts of about 13-20 meV observed as a function of the transferred momentum q∥a reflect a finite dispersion of the orbital excitations. This is puzzling since theoretical models based on superexchange interactions predict a dispersion only for q∥c. Furthermore, we demonstrate that RIXS at the O K edge is very sensitive to intersite excitations. At the O K edge, we observe excitations across the Mott-Hubbard gap and an additional feature at 0.4 eV, which we attribute to two-orbiton scattering, i.e., an exchange of orbitals between adjacent sites. Altogether, our results indicate that both superexchange interactions and the crystal field are important for a quantitative understanding of the orbital excitations in YVO3.